2015
DOI: 10.1007/s10661-015-4533-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal speciation in soil and health risk due to vegetables consumption in Bangladesh

Abstract: This study was conducted to investigate the contamination level of heavy metals in soil and vegetables, chemical speciation, and their transfer to the edible part of vegetables. Metals were analyzed using inductively coupled plasma mass spectrometer (ICP-MS). The ranges of Cr, Ni, Cu, As, Cd, and Pb in agricultural soils were 3.7-41, 3.9-36, 3.7-46, 2.3-26, 0.6-13, and 4.5-32 mg/kg, respectively. The metals were predominantly associated with the residual fractions of 39, 41, 40, 40, 34, and 41 % for Cr, Ni, Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 51 publications
2
32
1
1
Order By: Relevance
“…The contamination of agricultural soil and crops with heavy metals is one of the most serious environmental as well as ecological problems worldwide [16], especially in developing countries like Bangladesh [4,9]. Here, the assessment of health risk and daily dietary intake due to heavy metals based on the regular food consumption studies is very crucial for both the children and the adult [20]. Several studies showed an elevated level of heavy metals in human-edible food crops which are grown in the contaminated areas of Bangladesh and some other countries due to industrial activities such as power plants, ship breaking, and mining [9][10][11]16].…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of agricultural soil and crops with heavy metals is one of the most serious environmental as well as ecological problems worldwide [16], especially in developing countries like Bangladesh [4,9]. Here, the assessment of health risk and daily dietary intake due to heavy metals based on the regular food consumption studies is very crucial for both the children and the adult [20]. Several studies showed an elevated level of heavy metals in human-edible food crops which are grown in the contaminated areas of Bangladesh and some other countries due to industrial activities such as power plants, ship breaking, and mining [9][10][11]16].…”
Section: Introductionmentioning
confidence: 99%
“…The EF of an area indicates the relative enrichment in any contaminant when compared to pre-industrial soils from the same environment [10,11]. As soil pollution arising from brick kiln, the study area have raised attention due to its environmental pollution which is facing serious threats due to elemental pollution originated from the rapid expansion, congestion, and activities from brick kilns [12]. Several studies have reported the concentration of hazardous elements in agricultural soils due to brick kiln in Bangladesh [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The nug/sill ratios are often used for spatial heterogeneity and reflect the influence of regional factors (nature) and the role of non-regional factors (human factors). Soil is generally contaminated by heavy metals from two main sources: natural factors such as weathering, erosion of parent rocks, atmospheric deposition and volcanic activities; and anthropogenic activities such as sewage irrigation, addition of manures, fertilizers, and pesticides [24][25][26][27]. When C 0 / (C 0 +C) < 0.25, the variable space mutation gave priority to the structural variation (nature), and the variables have a strong spatial correlation.…”
Section: Data Processingmentioning
confidence: 99%